Exquisite morphology, highly emissive yellow Sr1.44Ba0.46SiO4:0.1Eu2+ phosphor synthesized by a liquid phase precursor process. (July 2017) - Humayoun, Usama Bin; Song, Young Hyun; Kwon, Seok Bin; Masato, Kakihana; Toda, Kenji; Sato, Yasushi; Masaki, Takaki; Yoon, Dae-Ho
Abstract: Yellow phosphors are the major components of contemporary solid-state lights. YAG:Ce 3+ is a widely adopted yellow phosphor component; however, it too has limitations. Here, we report the synthesis and application of a very highly efficient yellow-emitting orthosilicate phosphor. Yellow-emitting Sr1.44 Ba0.46 SiO4 :0.1Eu 2+ was synthesized by an unconventional cellulose template liquid phase precursor process (CTLPP). The naturally abundant and nonhazardous cellulose template facilitates efficient synthesis at lower temperatures. The synthesized phosphor was indexed to α-Sr2 SiO4 phase and exhibited broad excitation and broad emission with a peak at 545 nm, very high intensity, almost 130% of commercial YAG upon excitation at 450 nm. The morphology of the phosphors was also nearly spherical, which also enables their use in WLEDs. Use of non-stoichiometric Si precursors (i.e. Sr1.44 Ba0.46 Six O4 :0.1Eu 2+, x = 0.95, 1.0 and 1.05) in the process resulted in remarkable effects on the morphology (size and surface) and luminescent characteristics and exceptional quantum efficiencies of the phosphors. Highlights: We prepared yellow-emitting Sr1.44Ba0.46SiO4:0.1Eu2+ using a cellulose template liquid phase precursor. The nonstoichiometric Sr1.44Ba0.46SiO4:0.1Eu2+ also rendered an IQE of 95.8%. Our material can potentially serve as promising phosphors for LED applications.